THE LEGAL PROTECTION FOR A GOOD FAITH BUYER UNDER A COURT DECISION - Muhammad Faisal (Fakultas Hukum Universitas Gadjah Mada, 2015)
There are various principles given in Indonesian Civil Code (KUHPerdata) and HIR/RBg in providing legal protection on good faith purchaser, but all of these principles eventually dropped their pedestal on a judge’s verdict to decide whether or not the intention of the buyer is based on a good faith purchaser. There are also many factors that can influence the decision of a judge that can lead to different conceptions of the protection provided. In addition, the rapid development of the present law requires judges to review the general principles of law and also applying existing law theories in the making of their verdict. Permasalahan perlindungan hukum pembeli beritikad baik merupakan masalah yang cukup mendasar dalam hukum kita. Terdapat berbagai prinsip yang diberikan dalam KUHPerdata maupun HIR/RBg dalam mengupayakan perlindungan hukum pembeli beritikad baik, akan tetapi upaya-upaya tersebut pada akhirnya menjatuhkan tumpuannya pada putusan hakim untuk menilai beritikad baik atau tidaknya seseorang. Di sisi lain, terdapat banyak faktor yang mempengaruhi putusan seorang hakim sehingga apabila dikaitkan dengan itikad baik, dapat menimbulkan konsepsi yang berbeda-beda terhadap perlindungan yang diberikan. Selain itu, pesatnya perkembangan hukum sekarang ini mewajibkan hakim-hakim untuk mempelajari kembali asas-asas hukum serta menerapkan teori-teori hukum yang ada dalam membuat putusannya.